Customer Loyalty Based on Service Quality, Banking Image, and Fairness Mediating Role of Customer Satisfaction - Abdul Fatah Rusydi; Ridwan, Muhtadi; Ekowati, Vivin Maharani; Supriyanto, Achmad Sani; Johari, Fuadah Binti (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Technological advances have impacted intense business competition in the banking world, requiring all banks to compete in updating systems to maintain customer loyalty, which is essential to a business' success. Influencingtors influencing customer loyalty are service quality, banking image, and fairness. Purpose: The purpose of this study is to examine how customer satisfaction functions as a mediating factor between service quality, banking image, fairness and customer loyalty. Design/methodology/approach: Quantitative methods are used in this study. The population consists of Bank Muamalat customers. Accidental sampling was utilized as a research sampling method. The sample amounted to 210 respondents with research data using primary data. The SmartPLS 3.3 analysis tool was used to assist this research. Findings/Result: The findings of this study show that CARTER service quality can significantly improve customer loyalty at Bank Muamalat Malang. A favorable banking image has a strong positive impact on customer loyalty. Likewise, the Maqashid Syari'ah Index (MSI) fairness concept can have a direct impact on consumer loyalty. In addition, the study's findings suggest that customer happiness can mediate the impact of service quality, image, and fairness on customer loyalty. Conclusion: This study shows that service quality and banking image have a substantial impact on customer loyalty. At the same time, the concept of fairness has a substantial impact on customer loyalty. Customer satisfaction can mediate the impact of service quality, banking image, and the concept of fairness on customer loyalty. Originality/Value (State of The Art): This study attempts to explain service quality based on an Islamic perspective; it is hoped that this model development will reduce the scarcity of literature on service quality. Keywords: service quality, banking image, fairness, customer loyalty, customer satisfaction